2016
DOI: 10.1515/psicl-2016-0011
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting as a stressful activity: physiological measures of stress in simultaneous interpreting

Abstract: AbstractThe question of interpreter aptitude has been widely discussed in Interpreting Studies (e.g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 34 publications
3
40
0
9
Order By: Relevance
“…These findings are supported by Roziner and Shlesinger (2010, p. 219), who investigated remote interpreting at the European Parliament and concluded that "simultaneous interpreting is a particularly stressful occupation, as it requires the interpreter to simultaneously listen, analyse, comprehend, translate, edit and produce a speaker's utterance in real-time." Korpal (2016) investigated the causal relationship between a speaker's rate of delivery and the level of stress experienced by trainee interpreters and concluded that "simultaneous interpreting may indeed be considered a stressful activity" (Korpal 2016, p. 311). Bontempo and Napier (2011, p. 85) have described a "mini-explosion" of research on sign language (SL) interpreters.…”
Section: Previous Researchmentioning
confidence: 99%
“…These findings are supported by Roziner and Shlesinger (2010, p. 219), who investigated remote interpreting at the European Parliament and concluded that "simultaneous interpreting is a particularly stressful occupation, as it requires the interpreter to simultaneously listen, analyse, comprehend, translate, edit and produce a speaker's utterance in real-time." Korpal (2016) investigated the causal relationship between a speaker's rate of delivery and the level of stress experienced by trainee interpreters and concluded that "simultaneous interpreting may indeed be considered a stressful activity" (Korpal 2016, p. 311). Bontempo and Napier (2011, p. 85) have described a "mini-explosion" of research on sign language (SL) interpreters.…”
Section: Previous Researchmentioning
confidence: 99%
“…In order to overcome health risks faced by these students, EI interventions are believed to be useful for empowering them and helping them to employ functional coping strategies. Like health professionals, translators and interpreters can also be subject to stressful situations, both during their training and when practicing in real-life contexts (Bontempo & Malcolm, 2012;Korpal, 2016;Roziner & Shlesinger, 2010). They may be asked to interpret for patients in hospitals, for criminals in courts, or they may have to translate death certificates or autopsy reports.…”
Section: Emotional Intelligence and Sustainabilitymentioning
confidence: 99%
“…Bower (2015) pointed out the cause of work exhaustion that the requirement for an objective resulted in individual value excessively pursuing the work, not being able to eff ectively cope with it to generate working pressure and frustration, gradually perceiving emotional exhaustion, and facing with negative attitudes and reducing work motivation and achievement to further damage the work performance and physical health. Korpal (2016) regarded work exhaustion as the function of individual perceived pressure. Under long-term pressure, an individual might shrink back from or not be willing to devote to the work to result in physical, emotional, and attitude exhaustion and further aff ect the quality of work.…”
Section: Work Exhaustionmentioning
confidence: 99%